Kajian Arsitektur Berkelanjutan pada Resort Rock and Wreck di Pantai Tanjung Kelayang, Belitung - Jiemmy Adrian; Muchlisiniyati Safeyah (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2026)
Rock and Wreck Resort is a well-known tourist destination located at Tanjung Kelayang Beach, Belitung, Indonesia. The resort has become increasingly popular among both domestic and international tourists due to its pristine white-sand beach and tropical natural surroundings that offer tranquility and scenic beauty. The resort applies sustainable architecture, integrating environmental, social, and economic sustainability principles into its planning, design, and construction. This study aims to explore the key aspects of sustainable architecture and its application to buildings, including land use, energy efficiency, water conservation and waste management, building materials, health and comfort, and community involvement. The research method used is rationalistic qualitative, providing an in-depth understanding of the implementation of sustainable architecture at Rock and Wreck Resort. The findings indicate that the resort successfully applies sustainable architecture principles optimally, demonstrated through wise land use, energy efficiency, effective water conservation and waste management, the selection of environmentally friendly materials, and attention to the health and comfort of its occupants